2015
DOI: 10.4312/dp.42.1
|View full text |Cite
|
Sign up to set email alerts
|

The origins of pottery in East Asia: updated analysis (the 2015 state-of-the-art)

Abstract: Recent developments related to the emergence of pottery in East Asia and neighbouring regions are presented. According to a critical evaluation of the existing evidence, the oldest centres with pottery in East Asia are situated in South China (dated to c. 18 000 calBP), the Japanese Islands (c. 16 700 calBP), and the Russian Far East (c. 15 900 calBP). It is most likely that pottery-making appeared in these regions independently of each other. In Siberia, the earliest pottery now known isfrom the Transbaikal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Radiocarbon dating has since demonstrated that the oldest pottery layers date to the Late Glacial (e.g. Kuzmin 2015Kuzmin , 2017. Sites with pre-Holocene pottery assemblages are widely scattered across the RFE, and are now defined as representing the onset of an 'Initial Neolithic' that is defined by the appearance of pottery and some other Neolithic novelties like polished axes, bifacially retouched or polished projectiles, new types of scrapers and art objects (e.g.…”
Section: Regional Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiocarbon dating has since demonstrated that the oldest pottery layers date to the Late Glacial (e.g. Kuzmin 2015Kuzmin , 2017. Sites with pre-Holocene pottery assemblages are widely scattered across the RFE, and are now defined as representing the onset of an 'Initial Neolithic' that is defined by the appearance of pottery and some other Neolithic novelties like polished axes, bifacially retouched or polished projectiles, new types of scrapers and art objects (e.g.…”
Section: Regional Settingmentioning
confidence: 99%
“…16,000-10,000 years ago; hereafter -cal BP, e.g. Kuzmin 2015Kuzmin , 2017. Together with southern China and Japan, the RFE represents one of the three main clusters of early pottery production in East Asia, and there is now clear evidence that pottery was already in use at a range of sites on the lower and middle reaches of the Amur River from ca.…”
Section: Introductionmentioning
confidence: 99%
“…The invention of pottery in the late Pleistocene was likely a significant driver for developments in food processing 19,20 . Pottery vessels can often be placed in robust relative chronological sequences using typology and seriation, although obtaining precise and accurate radiocarbon dates from pottery is extremely challenging 2, 3,21 .…”
mentioning
confidence: 99%
“…Both types of firing produce irreversible changes in the clay body. The earliest invention of ceramic (pyro)technology in East Asia predates its appearance in the Near East by some ten millennia (Cohen 2013;Kuzmin 2015;Gibbs, Jordan 2016).…”
Section: The Origins Of Ceramic Technologies In Huntergatherer Societiesmentioning
confidence: 99%